2015
DOI: 10.1515/jcim-2014-0075
|View full text |Cite
|
Sign up to set email alerts
|

Effect ofWithania somnifera(Ashwagandha) root extract on amelioration of oxidative stress and autoantibodies production in collagen-induced arthritic rats

Abstract: The results showed that WSAq exhibited antioxidant and anti-arthritic activity and reduced inflammation in CIA rats and suggests the potential use of this plant in the treatment of arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…Ashwaganda has beneficial effects on diseases of cardiovascular nature (Ravindran et al, 2015a), obesity, diabetes, infection, cancer (Choi and Kim, 2015, Khazal et al, 2014, Rai et al, 2016), arthritis (Gupta and Singh, 2014, Khan et al, 2015) and gastric inflammation (Kim et al, 2016). The major constituent in Ashwaganda, identified as Withaferin A, itself is an inhibitor of HMG-CoA, angiotensinogen-converting enzyme, (Ravindran et al, 2015b) can lower total cholesterol, triglycerides, higher HDL/LDL ratios (Shukla et al, 2014) and reduce severity or incidence of myocardial infarction, (Khalil et al, 2015) stroke (Ahmad et al, 2015, Raghavan and Shah, 2015, Sood et al, 2015) and hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Ashwaganda has beneficial effects on diseases of cardiovascular nature (Ravindran et al, 2015a), obesity, diabetes, infection, cancer (Choi and Kim, 2015, Khazal et al, 2014, Rai et al, 2016), arthritis (Gupta and Singh, 2014, Khan et al, 2015) and gastric inflammation (Kim et al, 2016). The major constituent in Ashwaganda, identified as Withaferin A, itself is an inhibitor of HMG-CoA, angiotensinogen-converting enzyme, (Ravindran et al, 2015b) can lower total cholesterol, triglycerides, higher HDL/LDL ratios (Shukla et al, 2014) and reduce severity or incidence of myocardial infarction, (Khalil et al, 2015) stroke (Ahmad et al, 2015, Raghavan and Shah, 2015, Sood et al, 2015) and hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…The parts of medicinal plant W. somnifera consist of bioactive compounds like withanolides and withaferin A and thereby exhibit antioxidant and anti‐inflammatory property used as antirheumatoid. [ 185,186 ] The preclinical screening concluded that the powder extract of root part tends to have active phytoconstituents attributing an anti‐arthritic effect at a dose of 600 mg/kg and suppressing the rheumatoid symptoms. Therefore, the plant extract can be used as an adjuvant therapy.…”
Section: The Various Herbal Plants Used In the Treatment Of Rheumatoimentioning
confidence: 99%
“…The aqueous extract of Withania somnifera Dunal, a common ingredient of antiarthritic polyherbal formulations, reduces the levels of systemic oxidative stress in collagen-induced arthritis in rats: it diminishes the lipid peroxidation levels and glutathione-S-transferase activity and increases the glutathione content in plasma [ 137 ]. This plant extract diminishes the arthritic index and the production of C-reactive protein and antinuclear antibodies in an extent comparable to methotrexate [ 137 ]. The lignan eleutheroside E ((+)-syringaresinol diglucoside), the main active constituent of Acanthopanax senticosus , ameliorates arthritis severity in mice by inhibiting NF- κ B activity, inflammatory cell infiltration, pannus formation, cartilage damage, and bone erosion.…”
Section: The Use Of Natural Products As Therapeutic Adjuvants To Tmentioning
confidence: 99%